Pengaruh edukasi metode bernyanyi dan video animasi cuci tangan pakai sabun terhadap kemampuan mencuci tangan dengan benar pada siswa-siswi taman kanak -kanak - Bakti Herwanti; Christin Angelina Febriani; Fitri Eka Sari (Holistik Jurnal Kesehatan, 2022)
Hand washing in kindergarten school students using demonstration, song, and animated video Background: Awareness to maintain personal health must be instilled from an early age. Pre-school-age children have a habit of paying less attention to the proper use of handwashing. One method of health promotion about hand washing that is interesting for children is the singing and animated video.Purpose To determine the effect of using demonstration, song, and animated video about proper handwashing among kindergarten school studentsMethod: Quantitative research with two group pre-test post-test design. The population was all students at Hidayatullah Waydadi Kindergarten, Bandar Lampung City, and the samples were total population, as many as 46 students, divided by 2 groups, demonstration, song, and animated video. Each group consists of 23 participants. Data was collected with a checklist and observation sheets. The statistical test used Wilcoxon signed-rank test.Results: The finding of 46 participants, before having intervention, all participants were improperly in handwashing (100%), and after having the intervention of demonstration, song, of 18 (78%) had a properly in handwashing  and by an animated video of 19 (83%). Wilcoxon statistical test both groups showed p-value = 0.000 < (0.05).Conclusion: There was an effect of using demonstration, song, and animated video about proper handwashing among kindergarten school students. The result by using an animated video it was more effectiveSuggestion: It is necessary to apply to learn to use demonstrations, songs, and animated videos about properly and correctly handwashing among kindergarten school students. By using, animated video learning is easier to understand to the student.Keyword: Hand washing;  Kindergarten school students; Demonstration; Song; Animated videoPendahuluan: Kesadaran untuk menjaga kesehatan diri, harus ditanamkan sejak dini. Anak usia pra sekolah mempunyai kebiasaan kurang memperhatikan perilaku mencuci tangan. Salah satu metode promosi kesehatan tentang cuci tangan yang menarik untuk anak yaitu dengan metode bernyanyi dan video animasi.Tujuan: Untuk mengetahui pengaruh demonstrasi, bernyanyi dan vieo animasi terhadap kemampuan cuci tangan pada siswa-siswa taman kanak-kanak (TK).Metode:Penelitian kuantitatif dengan desain two group pre-test post-test. Populasinya adalah siswa-siswa TK Hidayatullah Waydadi, dan sampel menggunakan total populasi sebanyak 46 orang. Masing-masing grup berisi 23 partisipan. Pengumpulan data dengan lembar check list dan observasi. Uji statistik menggunakan uji Wilcoxon Signed Rank Test.Hasil: Diperoleh hasil dari 46 responden, sebelum intervensi seluruh responden tidak mampu melakukan tindakan cuci tangan dengan benar (100%), sesudah diberikan intervensi metode bernyanyi yang mampu melakukan tindakan cuci tangan dengan benar sejumlah 18 (78%) dan sejumlah 19 (83%) mampu melakukan cuci tangan engan benar melalui metode video animasi. Uji statistik Wilcoxon menunjukkan p value = 0,000 < α (0,05).Simpulan: Terdapat pengaruh edukasi metode bernyanyi dan metode video animasi cuci tangan pakai sabun terhadap kemampuan mencuci tangan pada siswa-siswa taman kanak-kanak (TK).Saran: Perlu diterapkan pembelajaran menggunakan demonstrasi, lagu, dan video animasi tentang cuci tangan yang baik dan benar di kalangan siswa sekolah TK dengan menggunakan video animasi pembelajaran lebih mudah dipahami oleh siswa.